2019
DOI: 10.1016/j.celrep.2019.01.074
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Compartmentalization in Neurons

Abstract: Graphical AbstractHighlights d Neural computation relies on compartmentalized dendrites to discern inputs d A method is described to systematically derive the degree of compartmentalization d There are substantially fewer functional compartments than dendritic branches d Compartmentalization is dynamic and can be tuned by synaptic inputs In BriefMany neuronal computations rely on the compartmentalization of dendrites into functional subunits. Wybo et al. investigate the number of these subunits that can coexis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 85 publications
0
45
0
Order By: Relevance
“…The fine-scale functional organization of the presynaptic circuitry implies that DSGCs may be capable of highly parallel processing of motion information. Modeling studies suggest that nonlinear integration can occur independently in highly branched dendritic structures (Koch et al, 1982;Rall, 1964;Wybo et al, 2019). Moreover, local inhibitory input dramatically increase the ability of neighboring sites to function as independent units (Wybo et al, 2019), as we have observed for DSGCs.…”
Section: Implications For Local Dendritic Integrationmentioning
confidence: 59%
See 3 more Smart Citations
“…The fine-scale functional organization of the presynaptic circuitry implies that DSGCs may be capable of highly parallel processing of motion information. Modeling studies suggest that nonlinear integration can occur independently in highly branched dendritic structures (Koch et al, 1982;Rall, 1964;Wybo et al, 2019). Moreover, local inhibitory input dramatically increase the ability of neighboring sites to function as independent units (Wybo et al, 2019), as we have observed for DSGCs.…”
Section: Implications For Local Dendritic Integrationmentioning
confidence: 59%
“…Modeling studies suggest that nonlinear integration can occur independently in highly branched dendritic structures (Koch et al, 1982;Rall, 1964;Wybo et al, 2019). Moreover, local inhibitory input dramatically increase the ability of neighboring sites to function as independent units (Wybo et al, 2019), as we have observed for DSGCs. Although our data cannot speak to whether each site is independently 'integrating' synaptic input in the sense of triggering a Na + spike, we can say that direction-selective information is present at each site, which could certainly support local spike generation with high directional accuracy.…”
Section: Implications For Local Dendritic Integrationmentioning
confidence: 59%
See 2 more Smart Citations
“…[50][51][52][53] Analysis of voltage spread shows a strong attenuation of voltage at dendritic branch-points, supporting the view of an electric dendritic compartment. 54 Dendrites contain ionic conductances capable of generating non-linear active dendritic events-dendritic spikes-in response to local synaptic activity, placing dendrites as the integration unit. Dendritic activated glutamate receptors and voltage-gated calcium and sodium channels can be activated by synchronous activation of spatially clustered synapses generating electric fields that propagate along the entire dendritic branch.…”
Section: Synaptic Tagging and Capture And The Compartmentalization mentioning
confidence: 99%